NEW SPECIES OF FRASNIAN CONODONTS FROM THE MIDDLE TIMAN - Kuzmin A.V. (My University, 2001)
Abstract-The Frasnian conodont assemblages from the Ust'-Yarega and Kraipol formations of the Middle Timan are discussed. Seven new species of the genus Polygnathus are described: P. illustris, P. land, P. pizhmensis, P. reimersi, P. sculptilis, P. spams, and P. yaranicus.
Keywords: Frasnian; Paleozoic::Devonian::Upper::Frasnian; Палеозой::Девонская::Верхний::Франский